Environmentally friendly concrete
By blending the filler made of rubber particles, bentonite and highly absorbent resin with waste concrete and combining the electrostatic effect of polycarboxylic acid water reducing agent, the strength and ease caused by microcracks and roughness of the surface of waste concrete are solved. The problem of degradation of properties achieves high strength, excellent and ease of concrete.
Patent Information
- Application Number
- CN202310343806.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-04-03
AI Technical Summary
In the prior art, there are microcracks and roughness on the surface after the waste concrete is broken, resulting in a decrease in strength and ease of concrete, and a high porosity, which affects the overall performance of concrete.
Fillers made of rubber particles, bentonite and highly absorbent resins are blended with waste concrete and ball milled. The filler fills the pores of waste concrete after water absorption expansion, and combines the electrostatic effect of polycarboxylic acid water reducing agent to improve the concrete. liquidity and dispersion.
It effectively reduces the porosity of concrete, improves the strength and hardness of concrete, enhances its ease and flowability, and improves the overall performance of environmentally friendly concrete.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and more specifically, to an environmentally friendly concrete. Background Art
[0002] Concrete materials have brought negative impacts on the environment. For example, the carbon dioxide and sulfur-containing gases emitted by burning calcium carbonate in cement manufacturing form acid rain, which produces a greenhouse effect and further affects the environment. According to a survey, one-third of urban noise comes from construction, of which the vibration noise of concrete pouring accounts for the majority. In terms of the characteristics of concrete itself, it is hard and brittle, and its color is dark, giving people a rough, hard and cold feeling. The living space made of concrete is monotonous in color, lacks air permeability and water permeability, and has poor temperature and humidity regulation performance. The high density of concrete buildings and paved roads in cities causes the temperature of the city to rise.
[0003] Environmentally friendly concrete must not only meet the requirements of being a structural material, but also minimize the load and adverse effects on the earth's environment, and be able to coordinate with nature and coexist with the environment. Therefore, as the construction material used by humans in the largest amount, the development direction of concrete must inevitably be to meet the needs of modern people, take environmental factors into consideration, and be conducive to resource and energy conservation and ecological balance.
[0004] In the prior art, a Chinese invention patent application document with application number CN201810412211.4 discloses a waste concrete blended recycled concrete, which comprises the steps of ball-milling and sieving the waste concrete to obtain refined waste concrete, mixing the refined waste concrete with hydrochloric acid at a mass ratio of 1:30-50, filtering, and drying to obtain pretreated waste concrete, and roasting and cooling the pretreated waste concrete to obtain modified waste concrete; by weight, placing 20-30 parts of modified waste concrete, 20-30 parts of cement, 30-40 parts of aggregate, 3-5 parts of water reducer, 3-5 parts of silane coupling agent, 3-5 parts of dopamine solution with a mass concentration of 2.5 mg / mL, 3-5 parts of triethanolamine, 3-5 parts of sepiolite, 3-5 parts of carbomer, and 3-5 parts of lees in a mixer, stirring and mixing to obtain waste concrete blended recycled concrete.
[0005] With regard to the above-mentioned related technologies, after the waste concrete is crushed, there are many micro cracks on the surface, the surface is rough, and the water absorption rate is large, which reduces the workability of the concrete, and the porosity is high after hardening, and the strength of the concrete is low. Summary of the invention
[0006] In order to improve the strength of concrete, the present application provides an environmentally friendly concrete.
[0007] In the first aspect, the present application provides an environmentally friendly concrete, which adopts the following technical solution:
[0008] An environmentally friendly concrete comprises the following raw materials in parts by weight:
[0009] 22-30 parts of cement;
[0010] 21-27 parts of river sand;
[0011] 18-22 pieces of stone;
[0012] 20-29 parts of waste concrete;
[0013] 3-5 parts of water reducing agent;
[0014] 13-17 parts of filler;
[0015] 25-30 parts water;
[0016] The filler is made of rubber particles, bentonite and highly water-absorbent resin.
[0017] By adopting the above technical solution, the waste concrete is crushed and used as a substitute for cementitious materials to replace part of the cement. After the waste concrete is crushed into powder, there are many micro cracks on the surface, the surface is rough, and large pores will appear after the concrete hardens. The pores of the waste concrete are filled and blocked by adding fillers. The fillers are made of rubber to tightly connect bentonite and super absorbent resin together and are located in the pores of the waste concrete. When in contact with water, the bentonite and super absorbent resin will absorb water and expand. The expanded filler will fully fill the pores of the waste concrete, ensuring that the porosity of the concrete is reduced after hardening. At the same time, the bentonite and super absorbent resin are bonded together under the action of rubber, which also increases the hardness of the filler, thereby enhancing the strength of the concrete.
[0018] Preferably, the water reducer is a polycarboxylate water reducer.
[0019] By adopting the above technical solution, the surface of the waste concrete is rough after being crushed. After adding water, the workability and fluidity will deteriorate. The polycarboxylate water-reducing agent will be adsorbed on the surface of cement particles and waste concrete powder through electrostatic action, so that the surfaces of cement particles and waste concrete powder particles are negatively charged, thereby improving their fluidity and dispersibility under the action of electrostatic repulsion. At the same time, the polycarboxylate water-reducing agent also has a steric hindrance effect, which can further increase its fluidity and workability and improve the strength of concrete.
[0020] The carboxylate groups in the polycarboxylate water-reducing agent and the calcium ions in the cement can form a complex, which reduces the crystallization rate of calcium hydroxide and the formation of CSH gel, thereby delaying the cement hydration process and having a certain retarding effect, so that the fresh concrete can maintain its plasticity for a longer time.
[0021] Preferably, the weight ratio of the particle size ranges of the waste concrete is (0.5mm-2mm): (2mm-10mm): (10 mm -15 mm )=(1.2-1.6):(1.4-1.8):1.
[0022] By adopting the above technical solution, the waste concrete is crushed into powder particles of three particle size ranges, and then used with cement in a weight ratio of (0.5mm-2mm):(2mm-10mm):(10mm-15mm)=(1.2-1.6):(1.4-1.8):1, which can best replace cement and achieve the purpose of environmental protection.
[0023] Preferably, based on the weight of the environmentally friendly concrete, the filler includes:
[0024] 20-24 parts of rubber particles;
[0025] 5-9 parts of bentonite;
[0026] 10-14 parts of super absorbent resin.
[0027] By adopting the above technical scheme, both bentonite and super absorbent resin have the ability to absorb water and expand. The bentonite particles themselves are composed of small flaky crystals. This flaky crystal structure allows water molecules to enter, causing the crystals to absorb water and expand. However, the expansion rate of conventional bentonite is low. At this time, the super absorbent resin further absorbs water and expands. The expansion rate of the super absorbent resin is much higher than that of bentonite. It can be used in combination with bentonite, so as to seal the pores of the waste concrete as well as possible, thereby enhancing the strength and hardness of the waste concrete.
[0028] Preferably, the filler further comprises 4-8 parts of modified boehmite; 8-12 parts of white carbon black; and 0.5-1.1 parts of silane coupling agent; the modified boehmite is boehmite with cellulose grafted on the surface.
[0029] By adopting the above technical scheme, boehmite grafted with cellulose and white carbon black can generate a three-dimensional network structure by heating reaction under the action of silane coupling agent. The three-dimensional network structure can fix the expanded bentonite in the system in the filler, thereby improving the mechanical properties of the bentonite after absorbing water.
[0030] Preferably, the preparation method of the filler is:
[0031] Step 1: Take appropriate amounts of modified boehmite and white carbon black in a mass ratio of 1:(1.2-1.8), mix and crush the modified boehmite and white carbon black into a mixed powder, add a silane coupling agent into the mixed powder and stir evenly to obtain a mixture A;
[0032] Step 2: Add the rubber particles into a plasticizer and plasticize at 50-70°C for 30-60 minutes to obtain plasticized rubber;
[0033] Step 3: Add the mixture A obtained in the first step to the plastic compound obtained in the second step, and add bentonite and super absorbent resin at the same time, mix at 80-120° C. for 20-30 minutes to obtain a plastic compound, and extrude the obtained plastic compound into granules through an extruder to obtain a filler.
[0034] By adopting the above technical scheme, the modified boehmite, white carbon black and silane coupling agent are evenly mixed, so that the silane coupling agent can evenly adhere to the surface of the modified boehmite and white carbon black, and then the rubber is plasticized to obtain plasticized rubber, and the mixture A, plasticized rubber, bentonite and super absorbent resin are mixed. During the mixing process, the silane coupling agent is heated and fully contacts and reacts with the modified boehmite and white carbon black, thereby generating a three-dimensional network structure between the fillers, and this three-dimensional network structure can fix the bentonite particles, thereby enhancing the hardness and strength of the bentonite after water absorption and expansion, and improving the strength of the concrete.
[0035] Preferably, the particle size of the filler is in the range of 90-150 nm.
[0036] By adopting the above technical solution, limiting the particle size range of the filler to 90-150nm can allow the filler to better adhere to the pores and gaps in the waste concrete, play a better filling role, and better enhance the strength of the concrete.
[0037] In a second aspect, the present application provides a method for preparing environmentally friendly concrete, which adopts the following technical solution:
[0038] A method for preparing environmentally friendly concrete, the preparation steps are as follows:
[0039] S1: Blend the filler and the waste concrete, add zirconia balls and mill for 15-20 hours, sieve the milled mixture, and collect the mixture on the sieve;
[0040] S2: Mix cement, river sand, stone and the waste concrete collected in S1, add water reducing agent, and add water in batches to stir and mix to obtain environmentally friendly concrete.
[0041] By adopting the above technical scheme, the filler and the waste concrete are mixed and ball-milled, and the filler particles are filled into the pores and gaps of the waste concrete. Then, the filler and the waste concrete particles are mixed with cement, river sand, stone and water reducing agent, and water is added for stirring to obtain concrete.
[0042] In summary, this application has the following beneficial effects:
[0043] 1. The filler is prepared from rubber particles, bentonite and super absorbent resin. The rubber particles serve as a carrier and have excellent toughness. During the process of bentonite and super absorbent resin absorbing water and swelling, the bentonite and super absorbent resin can be tightly connected, so that the filler can fully fill the gaps and pores after absorbing water and swelling, thereby reducing the porosity of the waste concrete, reducing the porosity of the final concrete, and improving the strength and hardness of the concrete.
[0044] 2. Add modified boehmite, white carbon black and silane coupling agent. The modified boehmite is boehmite grafted with cellulose. Boehmite grafted with cellulose and white carbon black can generate a three-dimensional network structure by heating reaction under the action of silane coupling agent. The three-dimensional network structure can fix the expanded bentonite in the system in the filler, thereby improving the mechanical properties of the bentonite after absorbing water.
[0045] 3. After crushing the waste concrete into powder particles of three particle size ranges, they can be used together with cement in a weight ratio of (0.5mm-2mm):(2mm-10mm):(10mm-15mm)=(1.2-1.6):(1.4-1.8):1 to best replace cement, thereby achieving the purpose of environmental protection. DETAILED DESCRIPTION
[0046] The present application is further described in detail below in conjunction with embodiments.
[0047] The sources of raw materials used in this application are as follows:
[0048] Preparation example of filler
[0049] Preparation Example 1
[0050] Preparation method of filler:
[0051] Step 1: Take 6 kg of modified boehmite and 10 kg of white carbon black, mix and crush the modified boehmite and white carbon black into a mixed powder, add 0.8 kg of silane coupling agent into the mixed powder and stir evenly to obtain a mixture A;
[0052] Step 2: Add 22 kg of rubber pellets into a plasticizer and plasticize at 70°C for 45 minutes to obtain plasticized rubber;
[0053] Step 3: Add the mixture A obtained in the first step to the plastic compound obtained in the second step, and add 7 kg of bentonite and 12 kg of super absorbent resin at the same time, mix at 100°C for 30 minutes to obtain a plastic compound, and extrude the obtained plastic compound into granules through an extruder to obtain a filler.
[0054] Preparation Example 2
[0055] Preparation method of filler:
[0056] Step 1: Take 4 kg of modified boehmite and 8 kg of white carbon black, mix and crush the modified boehmite and white carbon black into a mixed powder, add 0.5 kg of silane coupling agent into the mixed powder and stir evenly to obtain a mixture A;
[0057] Step 2: Add 20 kg of rubber pellets into a plasticizer and plasticize at 70°C for 45 minutes to obtain plasticized rubber;
[0058] Step 3: Add the mixture A obtained in the first step to the plastic compound obtained in the second step, and add 5 kg of bentonite and 10 kg of super absorbent resin at the same time, mix at 100°C for 30 minutes to obtain a plastic compound, and extrude the obtained plastic compound into granules through an extruder to obtain a filler.
[0059] Preparation Example 3
[0060] Preparation method of filler:
[0061] Step 1: Take 8 kg of modified boehmite and 12 kg of white carbon black, mix and grind the modified boehmite and white carbon black into a mixed powder, add 1.1 kg of silane coupling agent into the mixed powder and stir evenly to obtain a mixture A;
[0062] Step 2: Add 24 kg of rubber pellets into a plasticizer and plasticize at 70°C for 45 minutes to obtain plasticized rubber;
[0063] Step 3: Add the mixture A obtained in the first step to the plastic compound obtained in the second step, and add 9 kg of bentonite and 14 kg of super absorbent resin at the same time, mix at 100°C for 30 minutes to obtain a plastic compound, and extrude the obtained plastic compound into granules through an extruder to obtain a filler.
[0064] Preparation Example 4
[0065] Step 1: Take 6 kg of boehmite and 10 kg of white carbon black, mix the boehmite and white carbon black and grind them into mixed powder to prepare mixture A;
[0066] Step 2: Add 22 kg of rubber pellets into a plasticizer and plasticize at 70°C for 45 minutes to obtain plasticized rubber;
[0067] Step 3: Add the mixture A obtained in the first step to the plastic compound obtained in the second step, and add 7 kg of bentonite and 12 kg of super absorbent resin at the same time, mix at 100°C for 30 minutes to obtain a plastic compound, and extrude the obtained plastic compound into granules through an extruder to obtain a filler.
[0068] Example
[0069] Example 1
[0070] Preparation method of environmentally friendly concrete:
[0071] S1: 15kg of filler and 25kg of waste concrete are mixed, 8.75kg of waste concrete with a particle size of 0.5mm-2mm, 10kg of waste concrete with a particle size of 2mm-10mm, and 6.25kg of waste concrete with a particle size of 10mm-15mm. Zirconia balls are added and milled for 20 hours, and the milled mixture is passed through a 0.5mm sieve, and the mixture on the sieve is collected;
[0072] S2: 26 kg of cement, 24 kg of river sand, 20 kg of stone and the waste concrete collected in S1 are mixed and 4 kg of water reducing agent is added, and 27 kg of water is added in batches and stirred to obtain environmentally friendly concrete.
[0073] The filler prepared in Preparation Example 1 is used as the raw material; the water reducer is a polycarboxylic acid water reducer.
[0074] Example 2-3
[0075] An environmentally friendly concrete, which is different from Example 1 in that the raw material components and their corresponding weight proportions are shown in Table 1.
[0076] Table 1 Raw materials and their weights in Examples 1-3 (kg)
[0077] Components Example 1 Example 2 Example 3 cement 26 22 30 river sand 24 27 21 stone 20 22 18 Waste concrete 25 20 29 Water reducing agent 4 5 3 Fillers 15 13 17 water 27 30 25
[0078] Example 4
[0079] An environmentally friendly concrete, which is different from Example 1 in that the raw material is the filler prepared in Preparation Example 2.
[0080] Example 5
[0081] An environmentally friendly concrete, which is different from Example 1 in that the raw material is the filler prepared in Preparation Example 3.
[0082] Example 6
[0083] An environmentally friendly concrete, which is different from Example 1 in that the particle size of the waste concrete ranges from 0.5 to 15 mm.
[0084] Comparative Example
[0085] Comparative Example 1
[0086] An environmentally friendly concrete, which is different from Example 1 in that no filler is added.
[0087] Comparative Example 2
[0088] An environmentally friendly concrete, which is different from Example 1 in that the filler comprises:
[0089] 20-24 parts of rubber particles; 5-9 parts of bentonite; 10-14 parts of super absorbent resin; the preparation method of the filler is as follows: the first step: adding 22kg of rubber particles into a plasticator, plasticating for 45 minutes at 60°C to obtain a plasticized rubber; the second step: adding 7kg of bentonite and 12kg of super absorbent resin to the plasticized rubber obtained in the first step, mixing at 100°C for 25 minutes to obtain a mixed rubber, and extruding the obtained mixed rubber into granules through an extruder to obtain the filler.
[0090] Comparative Example 3
[0091] An environmentally friendly concrete, which is different from Example 1 in that the raw material is the filler prepared in Preparation Example 4.
[0092] Performance testing
[0093] 1. Compressive strength test method
[0094] First, check the appearance of the specimen. Measure the size of the specimen and calculate the compressive area of the specimen. Next, place the specimen at the center of the lower pressure plate of the material testing machine. The compressive direction of the specimen should be perpendicular to the expansion direction of the product. Start the testing machine. When the upper pressure plate is close to the specimen, adjust the ball seat to make the contact balanced. Apply load continuously and evenly at a speed of (2.0±0.5) kN / s until the specimen is destroyed. Record the failure load (p1). Set multiple groups of test blocks, calculate the compressive strength using the following formula, and find the average value.
[0095] Compressive strength calculation formula:
[0096]
[0097] f ∝ ——Compressive strength of specimen (MPa)
[0098] p1——Failure load (N)
[0099] A1——Test piece pressure area (mm 2 )
[0100] The length, width and height of the test block are set to 100 mm.
[0101] 2. Flexural strength test method
[0102] First, check the appearance of the specimen, measure its width and height in the middle of the specimen, accurate to 1mm, place the specimen on the bending support roller, with a fulcrum spacing of 300mm, start the testing machine, and when the pressure roller is close to the specimen, adjust the pressure roller and the support roller to ensure balanced contact. The dimensional deviation of all spacings should not exceed ±1mm. The two support rollers and two pressure rollers in contact with the specimen of the testing machine should have an arc-shaped top surface with a diameter of 30mm and should be at least 10mm longer than the width of the specimen. Three of them (1 support roller and two pressure rollers) should be able to roll and tilt back and forth as much as possible. Apply load continuously and evenly at a speed of (0.20±0.05) kN / s until the specimen is destroyed. Record the failure load (p) and failure position. Set multiple groups of test blocks, calculate the flexural strength using the following formula, and find the average value. :
[0103] Flexural strength calculation formula:
[0104]
[0105] f f ——Flexural strength of specimen (MPa)
[0106] p——Failure load (N)
[0107] b——Test piece width (mm)
[0108] h——Test piece height (mm)
[0109] L——Span of supports (mm), accurate to 1mm.
[0110] The length, width and height of the test block were set to 400 mm, 100 mm and 100 mm respectively.
[0111] Table 2
[0112] Compressive strength(MPa) Flexural strength(MPa) Example 1 13.3 1.95 Example 2 12.7 1.87 Example 3 12.9 1.90 Example 4 12.7 1.88 Example 5 12.7 1.86 Example 6 12.2 1.79 Comparative Example 1 6.4 1.45 Comparative Example 2 8.8 1.52 Comparative Example 3 9.3 1.54
[0113] According to the combination of Example 1 and Comparative Example 1, and referring to the data in Table 2, after the filler is added in Example 1, the filler is filled in the pores and gaps of the waste concrete. When the concrete is mixed, the volume of the filler will increase after the reaction with water. At the same time, under the action of the polycarboxylate water-reducing agent, the dispersion effect in the concrete system is better, and the hardness and strength of the concrete are greatly improved.
[0114] According to the combination of Example 1 and Comparative Example 2, and referring to the data in Table 2, the difference between Comparative Example 2 and Example 1 lies in the change of the components of the filler. The filling concentrate lacks the addition of modified boehmite and white carbon black. The modified boehmite is boehmite with cellulose grafted on the surface. The boehmite grafted with cellulose and white carbon black can generate a three-dimensional network structure by heating reaction under the action of a silane coupling agent. The three-dimensional network structure can fix the expanded bentonite in the system in the filler, thereby improving the mechanical properties of the bentonite after absorbing water, thereby further improving the strength of the concrete.
[0115] According to the combination of Example 1 and Comparative Example 3, and referring to the data in Table 2, the difference between Comparative Example 3 and Example 1 is that the raw material used is the filler prepared in Preparation Example 4, and the difference between the filler prepared in Preparation Example 4 and the filler prepared in Preparation Example 1 is that the boehmite is ordinary boehmite. Compared with the modified boehmite with cellulose grafted on the surface, ordinary boehmite has fewer surface hydroxyl and carboxyl groups and cannot form a three-dimensional network structure with white carbon black, so the improvement effect in hardness and strength is not as good as that in Example 1.
[0116] According to the combination of Example 1 and Example 6, and referring to the data in Table 2, the difference between Example 6 and Example 1 is that Example 6 only limits the particle size of the waste concrete, but does not further limit the weight of the gradation. When the weight of the gradation of the waste concrete changes, its role in replacing cement in the concrete system decreases, thereby affecting the hydration reaction of the concrete during the mixing process, thereby causing the final strength of the concrete to decrease.
[0117] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An environmentally friendly concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 22-30 parts of cement; 21-27 parts of river sand; 18-22 pieces of stone; 20-29 parts of waste concrete; 3-5 parts of water reducing agent; 13-17 parts of filler; 25-30 parts water; Based on the weight of the environmentally friendly concrete, the filler includes: 20-24 parts of rubber particles; 5-9 parts of bentonite; 10-14 parts of super absorbent resin; 4-8 parts of modified boehmite; 8-12 parts of white carbon black; 0.5-1.1 parts of silane coupling agent; the modified boehmite is boehmite with cellulose grafted on the surface.
2. The environmentally friendly concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.
3. The environmentally friendly concrete according to claim 1, characterized in that: The weight ratio of each particle size range of the waste concrete is (0.5mm-2mm): (2mm-10mm): (10mm-15mm) = (1.2-1.6): (1.4-1.8):
1.
4. The environmentally friendly concrete according to claim 1, characterized in that: The preparation method of the filler is: Step 1: Take appropriate amounts of modified boehmite and white carbon black in a mass ratio of 1:(1.2-1.8), mix and crush the modified boehmite and white carbon black into a mixed powder, add a silane coupling agent into the mixed powder and stir evenly to obtain a mixture A; Step 2: Add the rubber particles into a plasticizer and plasticize at 50-70°C for 30-60 minutes to obtain plasticized rubber; Step 3: Add the mixture A obtained in the first step to the plastic compound obtained in the second step, and add bentonite and super absorbent resin at the same time, mix at 80-120° C. for 20-30 minutes to obtain a plastic compound, and extrude the obtained plastic compound into granules through an extruder to obtain a filler.
5. The environmentally friendly concrete according to claim 1, characterized in that: The particle size of the filler is in the range of 90-150 nm.
6. A method for preparing an environmentally friendly concrete according to any one of claims 1 to 5, characterized in that: The steps include: S1: Blend the filler and the waste concrete, add zirconia balls and mill for 15-20 hours, sieve the milled mixture, and collect the mixture on the sieve; S2: Mix cement, river sand, stone and the waste concrete collected in S1, add water reducing agent, and add water in batches to stir and mix to obtain environmentally friendly concrete.
Citation Information
Patent Citations
Waste concrete blended type regenerated concrete
CN108341642A
Environment-friendly high-strength concrete and preparation method thereof
CN113004009A